HUBUNGAN PENGARUH PENOLONG KELAHIRAN TERHADAP STATUS KELAHIRAN BAYI DENGAN KONTROL VARIABEL CONFOUNDING DI KABUPATEN BULELENG (STUDI KASUS: PUSKESMAS SUKASADA II) - DWIJAYANTHI, KADEK NOVIA; SRINADI, I GUSTI AYU MADE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 2 No 4 (2013), 2013)
One indicator of the Human Development Index (HDI) is the Infant Mortality Rate (IMR). IMR is lower HDI showed a better area when compared with other regions for different values ??of the same indicators. This study aims to determine the relationship between the birth attendants birth status and confounding variables that affect the status of births in Buleleng regency, with Sukasada II health center located in District Sukasada - Buleleng regency as the location of the observed cases of infant mortality. Results of analysis using logistic regression showed that (1) birth attendants, (2) maternal age, and (3) income household heads have a real influence on the status of the baby's birth. Birth status with medical birth attendants have the opportunity to live 2,427 times compared with non-medical birth attendants with controlled variables maternal age and income of the family head.
Keywords: IPM; Infant Mortality; Sukasada district; Buleleng regency; Logistic Regression